Organogenesis tanaman kacang hijau (Vigna radiata L.) pada beberapa konsentrasi zat pengatur tumbuh sitokinin dan giberelin secara in vitro - Sartia Hama; Lisa Widianti (Fakultas Pertanian Universitas Ichsan Gorontalo, 2019)
This study aims to determine the organogenesis of mung bean plants (Vigna radiata L.) in several concentrations of cytokine and gibberellin growth regulators In Vitro. The method used was a Completely Randomized Design (CRD) with 6 treatments, 4 replications so that there were 24 experimental units. The concentration level used was P0 = no treatment, P1 = 2.5 ppm BAP + 2 ppm GA, P2 = 3.5 ppm BAP + 3 ppm GA, P3 = 4.5 ppm BAP + 4 ppm GA, P4 = 5.5 ppm BAP + 5 ppm GA, P5 = 6.5 ppm BAP + 6 ppm GA. The results showed that the growth regulator BAP and GA that given to each treatment had no significant effect on all parameters, this was due to the lack of elements of nitrogen to stimulate plant growth. The most effective treatment was found in P4 with a concentration 5.5 ppm BAP + 5 ppm GA which had the average value of germination age of 2 days after planting, then the average value of plantlets height was 10.07 cm, the average number of roots and number of leaves were as much as 2 strands, while the number of plantlet weight was 0.35.